Shifting Speech Levels: Exploring Balinese Women’s Language in Inter-Caste Marriage Communication Contexts - Gusti Ayu Praminatih (Jurnal Kajian Bali (Journal of Bali Studies), 2021)
The general aims of this article are to engage and make sense of the Balinese women’s narratives. It is a case study based on the narratives of two Balinese women with different caste-based social backgrounds. Inter-caste communication requires different levels of speech between interlocutors. Consequently, there are two main objectives of this article. Firstly, to explore how life events occurred during inter-caste marriages, and through the telling of these events, the informants determine their levels of speech. Secondly, to examine the identity constructed by the informants through the levels of speech. This article employed ethnographic research, narrative analysis, and sociolinguistics theory. In-depth interviews were conducted to gain meaningful stories narrated by the informants. This study revealed that Balinese women constantly shifted their levels of speech in inter-caste marriage communication contexts. These levels of speech shifting also relate to the showing or negotiating identity construction of these Balinese women.